(untitled) (Research, Society and Development, 2022)
The aim of the paper is to verify the perception of authorities linked to Public Security about the performance of the Tactile Force of the 15th Regional Command in the fight against drug trafficking and its related crimes throughout the year 2021 in the city of Peixoto de Azevedo-MT. The qualitative methodology used descriptive analysis, through bibliographic review, document analysis and interview by guidelines. The results showed convergence between the implementation of the aforementioned tactical force and the improvement in criminal indicators in the city of Peixoto de Azevedo-MT, particularly that: the fight against drug trafficking and other crimes that surround this typical criminal offense (robbery, theft, illegal possession of firearms and homicide), carried out in an integrated manner by the security institutions, contributed to the drop in criminal indicators in the city of interest; in the perception of the interviewees, the tactical force was pointed out in an extremely positive way, for the actions carried out in the approaches and operations, in the seizures of firearms and narcotics, in the arrest of lawbreakers linked to drug trafficking and criminal factions; in the perception of the interviewees, the need to strengthen the tactical force of the analyzed regional was observed, since, even with a reduced number, it manages to bring favorable results in the context of public security.